Sir John Salmond and the Moral Agency of the State - McHugh, P G (Victoria University of Wellington Law Review, 2008)
New Zealand scholars have yet to develop a "tradition" of writing legal history outside the historiographically problematic field of Treaty claims. This essay uses Sir John Salmond as emblematic of the methodological features that such a tradition might carry. Any self-congratulatory and Whiggish vision of a good-hearted people incapable of anything other than a fundamentally decent past – itself a fiction punctured by the Treaty claims processes – should be discarded. Instead the New Zealand constitutional and legal system should be seen as a site of ongoing struggle, reflection and constant engagement amongst a series of actors whose thought – so much as that was articulated – is to be regarded as important as their action. A non-corrupt legal system is not the outcome of a complacent so much as vigilant past. Sir John Salmond's concern with the moral agency of the State not only placed him inside the mainstream of early twentieth century political thought, its "Idealist" thread in particular. It also underpinned his intendancy of the Crown Law Office, as Dr Hickford's subsequent (and important) essay demonstrates.